The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/5859415
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CYP2A6 and CYP2C8 in Tumor Tissues Is Linked to Worse Overall Survival and Recurrence-Free Survival from Hepatocellular Carcinoma

Abstract: Objective This study aimed to evaluate the links between CYP450 family genes in tumor tissues and hepatocellular carcinoma (HCC) outcomes. Methods Gene Expression Omnibus (GEO) databases GSE14520 and GSE36376 were used to identify differential expressed CYP450 genes between tumor and nontumor tissues and related to HCC clinicopathological features and survivals. Results Seven CYP450 genes including CYP1A2, CYP2A6, CYP2C8, CYP2C9, CYP2E1, CYP3A4, and CYP4A11 were downregulated in tumor tissues, which were valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
6
23
0
Order By: Relevance
“…Thus, Trujillo-Paolillo et al [51] have demonstrated that Osteosarcoma biopsy specimens has lower CYP3A4 levels than normal bone specimens. Similar findings have been found for CYP3A4 in Hepatocellular Carcinoma tissues as compared to paired adjacent noncancerous liver tissues [52, 53].…”
Section: Discussionsupporting
confidence: 85%
“…Thus, Trujillo-Paolillo et al [51] have demonstrated that Osteosarcoma biopsy specimens has lower CYP3A4 levels than normal bone specimens. Similar findings have been found for CYP3A4 in Hepatocellular Carcinoma tissues as compared to paired adjacent noncancerous liver tissues [52, 53].…”
Section: Discussionsupporting
confidence: 85%
“…The expression levels of CYP2A6 and CYP2A7 are lower in patients with hepatitis B virus and HCV than those in healthy people [41]. Moreover, patients with HCC with downregulated CYP2A6 exhibit the worse OS [42]. In the present study, the expression levels of CYP2A6 and CYP2A7 were low and negatively correlated with tumor stages and grades.…”
Section: Discussionsupporting
confidence: 45%
“…Studies have pointed out that CYP450 family genes are signi cantly associated with liver disease and liver cancer. For example, the downregulation of CYP2A6 and CYP2C8 is related to the overall survival and recurrence rates of liver cancer [38]. Additionally, the high expression of CYP4A11 is associated with a better prognosis in patients with liver cancer [39], and CYP activity is affected in varying degrees in patients with liver brosis or cirrhosis.…”
Section: Discussionmentioning
confidence: 99%